2013
DOI: 10.1371/journal.pone.0050573
|View full text |Cite
|
Sign up to set email alerts
|

Could the New Body Shape Index Predict the New Onset of Diabetes Mellitus in the Chinese Population?

Abstract: BackgroundAnthropometric measures could predict the new onset of diabetes mellitus (DM). Recently, a new anthropometric measure (a body shape index, ABSI) was developed, and ABSI could predict premature mortality, even better than WC and BMI. The main aims of the study were to assess the DM predictive power of ABSI based on the follow-up data over 15 years collected from a general Chinese population.Methods and FindingsThe data were collected in 1992 and then again in 2007 from the same group of 711 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 15 publications
7
90
1
1
Order By: Relevance
“…This result is consistent with the finding that combination of BMI and WC performed better in explaining non‐abdominal, abdominal subcutaneous and visceral fat than BMI or WC alone . Since then, interest in the effectiveness of this new index has risen across countries . However, subsequent research revealed conflicting results regarding the predictability of ABSI for chronic diseases and mortality .…”
Section: Introductionsupporting
confidence: 85%
“…This result is consistent with the finding that combination of BMI and WC performed better in explaining non‐abdominal, abdominal subcutaneous and visceral fat than BMI or WC alone . Since then, interest in the effectiveness of this new index has risen across countries . However, subsequent research revealed conflicting results regarding the predictability of ABSI for chronic diseases and mortality .…”
Section: Introductionsupporting
confidence: 85%
“…A recent study showed that ABSI, WC and BMI had similar ability to predict diabetes onset [24]. There is also conflicting data on whether anthropometric indicators of abdominal obesity are useful in revealing hypertension risk, given the information on BMI [4], [8][10], [24]. In the present study, both WC and BMI were more strongly associated with the development of hypertension.…”
Section: Discussioncontrasting
confidence: 46%
“…They highlighted not only the crudeness of the BMI but also the importance of abdominal obesity. A recent study showed that ABSI, WC and BMI had similar ability to predict diabetes onset [24]. There is also conflicting data on whether anthropometric indicators of abdominal obesity are useful in revealing hypertension risk, given the information on BMI [4], [8][10], [24].…”
Section: Discussionmentioning
confidence: 99%
“…The approach used to compute ARI here for hazard of all-cause mortality could also be extended to derive risk indices customized for specific causes of death and morbidity outcomes such as heart disease, stroke, or diabetes, which could facilitate individualized cost-benefit consideration in deciding what medical interventions to undertake [6971]. One recent study found that anthropometric indices (ABSI and WC/ H ratio) were correlated with Framingham and SCORE 10-year cardiovascular risk estimates in a nationally representative Turkish sample [72], while another study found anthropometry-based indices (specifically ABSI) to predict cardiovascular disease in middle-aged and elderly Dutch adults as well as a risk model that included laboratory measurements [73], highlighting the potential for utilization of a combination of several readily obtained body measurements for cardiometabolic risk assessment.…”
Section: Discussionmentioning
confidence: 99%